2012
DOI: 10.1186/1749-8104-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Muscleblind homolog mbl-1 functions in neurons to regulate synapse formation

Abstract: BackgroundThe sequestration of Muscleblind splicing regulators results in myotonic dystrophy. Previous work on Muscleblind has largely focused on its roles in muscle development and maintenance due to the skeletal and cardiac muscle degeneration phenotype observed in individuals with the disorder. However, a number of reported nervous system defects suggest that Muscleblind proteins function in other tissues as well.ResultsWe have identified a mutation in the Caenorhabditis elegans homolog of Muscleblind, mbl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
7
36
0
Order By: Relevance
“…We then examined the development of ventral cholinergic synapses using a chromosomally integrated transgene that expresses GFP::RAB-3 from the cholinergic neuronspecific promoter unc-4 (Spilker et al 2012). We found that cholinergic synapses were present dorsally throughout development.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined the development of ventral cholinergic synapses using a chromosomally integrated transgene that expresses GFP::RAB-3 from the cholinergic neuronspecific promoter unc-4 (Spilker et al 2012). We found that cholinergic synapses were present dorsally throughout development.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, NMJ degeneration has been observed in diaphragm muscles in mouse models of DM (Panaite et al, 2008). Additionally, motor neurons derived from human DM ES cells fail to form mature neuromuscular connections with normal muscle (Marteyn et al, 2011), and worms deficient in neuronal muscleblind expression fail to form distal NMJs, implicating pre-synaptic dysregulation (Spilker et al, 2012). Secretion of proteins with important functions in muscle may also be affected in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown both Reelin and CLASP2 play direct roles in modulating neuronal polarization through the regulation of both Golgi shape and deployment into the leading process (Matsuki et al 2010; O’Dell et al, 2012; Beffert et al, 2012). In addition, CLASP-dependent nucleation of microtubules at the Golgi is required for directional cargo trafficking (Miller et al, 2009; Efimov et al, 2007).…”
Section: Discussionmentioning
confidence: 99%